Adiponectin, Leptin and Inflammatory Markers in HIV-associated Metabolic Syndrome in Children and Adolescents. Issue 2 (February 2017) - Espiau, María; Yeste, Diego; Noguera-Julian, Antoni; Soler-Palacín, Pere; Fortuny, Clàudia; Ferrer, Roser; Comas, Immaculada; Martín-Nalda, Andrea; Deyà-Martínez, Ángela; Figueras, Concepció; Carrascosa, Antonio
Abstract : Background: Metabolic syndrome (MetS) is more common in HIV-infected adults and children than in the general population. Adipocytokines and inflammatory markers may contribute to the pathophysiology of this condition and could be useful indices for monitoring MetS. The objective of this study was to provide information on the prevalence of MetS and investigate the role of adipocytokines and other biomarkers in this syndrome in HIV-infected pediatric patients. Methods: A cross-sectional study was conducted between October 2013 and March 2014 in the outpatient clinics of 2 tertiary pediatric referral hospitals. Fifty-four HIV-infected children and adolescents were included. MetS was defined according to the International Diabetes Federation and modified National Cholesterol Education Program Adult Treatment Panel III criteria. Measurements included anthropometry, waist circumference, blood pressure, fasting lipids, glucose and insulin, adiponectin, leptin, interleukin-6, vitamin D and C-reactive protein and clinical lipodystrophy assessment. Results: Among the total, 3.7% of patients met the International Diabetes Federation criteria for MetS and 7.4% met the National Cholesterol Education Program Adult Treatment Panel III criteria. C-reactive protein and leptin levels were significantly higher and adiponectin level significantly lower in patients with MetS, regardless of the criteria used. Insulin resistance was observed in 40.7% of patients; abnormal quantitative insulin sensitivity check index values were found in 88.9%. Eighteen patients (33.3%) had vitamin D deficiency. Conclusions: The prevalence of MetS was similar to that observed in larger cohorts of HIV-infected patients in our setting. Adipocytokine dysregulation seems to be related to MetS in HIV-infected children. A high percentage of patients showed insulin resistance, which should be strictly monitored.